Perilaku Merokok Pada Mahasiswi Fakultas Psikologi Universitas Muhammadiyah Surakarta - Afandi, Ardi Dwi, Aad Satria Permadi, S.Psi, MA (2016)
In today people see smoke everywhere, whether in the office, in the market or other public places or even among their own households, both men and women. in 2013 that the number of women smokers in Indonesia increased by 5 times more than men. There is a trend of increasing the number of female smokers while male smokers stable. Each year 1.5 million people died of smoking and the 25,000 people who die of them are passive smokers. In Indonesia, male smokers as much as 65.9% and 4.5% of women. Data Director General of Disease Control and Environmental Health, Ministry of Health, the number continues to rise, especially smokers perempuan.Tujuan this study describes the smoking behavior of student of the Faculty of Psychology University of Muhammadiyah Surakarta. The informants as many as five people selected by snowball sampling technique that is student of the Faculty of Psychology, University of Muhammadiyah Surakarta smoking with age range 17-25 years. The results showed that their motivation in student smoking behavior, and motivation is influenced by the presence of factors. The factors that influence the behavior of cigarette smoke is functioning in everyday life, which is related to feelings and psychological satisfaction. Factors associated addicted about the frequency of smoking and the effects of nicotine in the body. Social environmental factors related to maintaining the privacy and the influence of environmental modeling.